Rumah Toko Kolonial dan Bentuk Modernnya di Indonesia: Menelusuri Jejak Arsitektur yang Terputus - Shiber, Nahridzah Mahjubuh; Rizqiyah, Umara Hasmarani; Edar, Ahmad Nadhil; Jusbaeni, Jusbaeni (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2025)
The transformation of Indonesian shophouses reveals a decisive rupture between the spatial intelligence of their colonial predecessors and the sealed, utilitarian forms that now dominate urban areas. Through a visual analysis comparing colonial photographic archives from Batavia, Bandung, and Makassar (1900–1930) with modern shophouse imagery (2020–2024), this study reveals that the defining features of colonial shophouses, such as arcades, transitional emperan, inner courts, cross-ventilation pathways, and layered spatial sequences, have been systematically erased. This disappearance reflects an aesthetic shift and the loss of an ecological and social logic that enabled these buildings to negotiate the tropical climate, urban density and street-level activity. The findings show that modern shophouse cannot be seen as a natural progression of the colonial shophouse, but rather as a typological departure that has abandoned the organic, climatic and socio-urban relationships that have historically shaped Indonesia's commercial streetscapes.